(untitled) (Journal of Chemical Engineering, 2012)
This work proposes a new combination and proportion of chemicals available in the local market to prepare laundry detergent at low cost in context of Bangladesh. The proposed formula ensures good foaming and washing quality of the detergent that can compete the existing other laundry detergents in the market. The pH of the product is maintained at 10 which is close to that of other detergent powder being sold in market now. The cost analysis in accordance with the proposed formula shows that the production of 1 kg detergent powder costs 20-25 BDT; therefore, can be sold at a price lower than the other detergents available in market. The proposed formula can reduce the selling price of the detergent at 40-45 BDT, whereas the other companies are selling it from 50-140 BDT in the market. This offers a new scope to produce laundry detergent at a very low cost as well as good washing performance of the product using the locally available chemicals in Bangladesh. DOI: http://dx.doi.org/10.3329/jce.v26i1.10184 JCE 2011; 26(1): 50-53